EMPLOYEE SOCIALIZATION AS A DETERMINANT OF RETENTION: EVIDENCE FROM THE IT INDUSTRY IN PUNE. - Khandekar, Sarika Rajabhau; Mehtha, Vijayshri (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Employee socialisation and its impact on IT sector retention in Pune City is the focus of this study report. The term "employee socialisation" refers to a wide range of organisational techniques that help new recruits feel more at home and increase their dedication to the company. This study tests two main hypotheses: first, that socialisation programs have a good effect on employee retention in the IT industry in Pune; and second, that employees in this sector have a favourable perception of these programs. A quantitative technique was used to gather data from 200 workers of various IT organisations in Pune. The data was acquired using structured questionnaires. Orientation events, training sessions, and peer assistance were the most well-received socialisation initiatives, according to the study. There was a statistically significant correlation between more staff retention and favourable socialisation methods. A study found that employees were less likely to look for other jobs, more committed to staying with their current companies over the long run, and more likely to stay with their current employers after receiving good socialisation. These results highlight the significance of socialisation tactics in creating a welcoming workplace that encourages employees to stay. Researchers found that socialisation plays a crucial role in retaining employees, which has important implications for human resource professionals and company executives. Further study should be conducted to identify the exact aspects of socialisation that influence retention rates. It would also be beneficial to examine similar dynamics in many industries and areas to make the findings more applicable.